2009
DOI: 10.1111/j.1743-6109.2008.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sexual Dysfunction in Men with Storage and Voiding Lower Urinary Tract Symptoms

Abstract: Introduction Sexual dysfunction (SD) and lower urinary tract symptoms (LUTS) are highly prevalent in men and increase with age. Previous studies have shown that LUTS and SD are highly associated in men, but most have not distinguished between voiding and storage LUTS. Aims Assess impact of voiding and storage LUTS on recorded diagnosis of SD in men in U.K. general practice. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
1
27
2
1
Order By: Relevance
“…In contrast, another community-based study of 2,858 men found that the presence of ED was associated with the total IPSS, specifically the scores for the voiding, nocturia, and quality of life domains [19]. A practice-based study of 333 men showed that the prevalence of sexual dysfunction was significantly higher in patients with either storage or voiding LUTS than in men without LUTS [20]. This trend also appeared in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, another community-based study of 2,858 men found that the presence of ED was associated with the total IPSS, specifically the scores for the voiding, nocturia, and quality of life domains [19]. A practice-based study of 333 men showed that the prevalence of sexual dysfunction was significantly higher in patients with either storage or voiding LUTS than in men without LUTS [20]. This trend also appeared in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…Indeed, results from this important study essentially showed that going from mild to moderate, or moderate to severe LUTS, had a greater impact on ED than ageing by 10 years (Figure 1). Similarly, in a study involving patients in UK general practices (31), odds ratios for ED in patients with both storage and voidance LUTS were calculated to be 4.0 (95% CI: 3.4–4.8). From the ED perspective, a study in Finland involving over a 1000 men (32) calculated the relative risk of LUTS in patients with severe ED as 2.3 (95% CI: 1.4–3.8).…”
Section: Evidence In Support Of a Link Between Ed And Lutsmentioning
confidence: 99%
“…It has been observed that there is an independent relationship between LUTS/BPH and co-existing ED [19-23]. While increasing age is a known predictor of LUTS/BPH and ED separately, LUTS/BPH severity is an even better predictor of ED than increases in a patient's age [24], thus establishing an independent link between LUTS/BPH and ED [6]. …”
Section: Epidemiology In the Global Populationmentioning
confidence: 99%